2018
DOI: 10.18671/scifor.v46n119.13
|View full text |Cite
|
Sign up to set email alerts
|

Estimação, zoneamento e análise de sensibilidade da produtividade florestal de Eucalyptus no Nordeste do Estado de São Paulo através do modelo 3-PG

Abstract: O zoneamento da produtividade auxilia no processo de planejamento do uso da terra, através da seleção de locais adequados a cultura. O objetivo deste estudo foi estimar e zonear a produtividade do eucalipto no nordeste do estado do São Paulo e determinar os principais fatores limitantes da produtividade segundo o modelo (temperatura, geadas, déficit de pressão de vapor, agua no solo, e fertilidade do solo). A estimativa da produtividade foi feita utilizando-se o modelo 3-PG tendo como entradas os mapas de esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Therefore, our initial concern for performing an adequate data division between training and testing datasets was important before starting the machine-learning modeling but, above all, having defined a minimum threshold of observations in each leaf node, pruning the tree growth's every decision where a node had up to 1% of the training dataset, thus ensuring an appropriate total wood volume distribution for any climate, soil, and altitude conditions detected in the study area. Eucalyptus productivity zoning studies have shown that validation is a major part of modeling credibility, whether it is an empirical or a process-based model, from extremely localized applications, as presented by Almeida et al [69]; at the regional level by Lemos et al [70] and Attia et al [71]; and at continental level, as shown by Caldeira et al [72] and Elli et al [73]. Although these studies performed a simple validation of their methods, none of them presented uncertainties in the estimates.…”
Section: Decision-tree Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our initial concern for performing an adequate data division between training and testing datasets was important before starting the machine-learning modeling but, above all, having defined a minimum threshold of observations in each leaf node, pruning the tree growth's every decision where a node had up to 1% of the training dataset, thus ensuring an appropriate total wood volume distribution for any climate, soil, and altitude conditions detected in the study area. Eucalyptus productivity zoning studies have shown that validation is a major part of modeling credibility, whether it is an empirical or a process-based model, from extremely localized applications, as presented by Almeida et al [69]; at the regional level by Lemos et al [70] and Attia et al [71]; and at continental level, as shown by Caldeira et al [72] and Elli et al [73]. Although these studies performed a simple validation of their methods, none of them presented uncertainties in the estimates.…”
Section: Decision-tree Modelingmentioning
confidence: 99%
“…Forests 2023, 14, x FOR PEER REVIEW 15 of 24 ensuring an appropriate total wood volume distribution for any climate, soil, and altitude conditions detected in the study area. Eucalyptus productivity zoning studies have shown that validation is a major part of modeling credibility, whether it is an empirical or a process-based model, from extremely localized applications, as presented by Almeida et al [69]; at the regional level by Lemos et al [70] and Attia et al [71]; and at continental level, as shown by Caldeira et al [72] and Elli et al [73]. Although these studies performed a simple validation of their methods, none of them presented uncertainties in the estimates.…”
Section: Decision-tree Modelingmentioning
confidence: 99%